KUNCI KESUKSESAN REFORMASI BIROKRASI SINGAPURA: PEMBELAJARAN UNTUK PARA PEMBUAT KEBIJAKAN - Seno, Ramadhani Haryo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Focus this research is to describe the process of public sector reform in a country, by finding the sectrets success in carrying out transformation and reform in Singapura. Descriptive qualitative analysis by study literature and examining secondary data as a data collection method use in this research. The results show that there are four secrets success of public sector reform in Singapore: (1) zero tolerance for corruption; (2) meritocracy in appointing and promoting someone in public sector or political office and making meritocracy the national identity and ideology. (3) Providing decent and competitive salaries to attract "the best and the brightest" citizens to join the government to become civil services. (4) the rule of law to solve social and political problems in the country's.